Jurnalistik Foto di Era Digital: Antara Teknologi dan Etika - Darmawan, Ferry (Mediator, 2005)
The development of photography technology, which mounted on digital photography, has provided real challenge for traditional photography. Digital photography open up opportunity for photographer to transform and modify pictures taken by digital camera. This challenge also affected journalism photography. Viewed from the side of mass media technology, photography digital seemed to give many benefits for mass media industry. Digital photography beat traditional photography in terms of place and time. But one must keep in mind that journalism deals only with factual matters. A serious discussion over ethical issues concerning the practice of digital photography in journalism was necessary.